Caracterização morfológica de frutos e sementes e germinação de Allophylus edulis (St. Hil.) Radlk. e Drimys brasiliensis Miers. - Abreu, Daniela Cleide Azevedo de (2002)
Orientador : Antonio Carlos Nogueira